The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.toxrep.2021.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of persons with acute thallium poisoning

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The effects of Tl toxicity in human beings arise after a couple of weeks from its administration, with alopecia being the main symptom, firstly with hair loss, then complete baldness, followed by axillary and pubic hair loss. Thallium poisoning becomes troubling when other symptoms occur such as gastrointestinal problems (nausea, vomiting and diarrhea), peripheral and central nervous system disorders (dysesthesia, ataxia, tremors, convulsions, paralysis, sleeplessness, hallucinations, and delirium), and cardiac problems, such as tachycardia and hypotension, lethargy, and coma) [33,34].…”
Section: Thallium Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of Tl toxicity in human beings arise after a couple of weeks from its administration, with alopecia being the main symptom, firstly with hair loss, then complete baldness, followed by axillary and pubic hair loss. Thallium poisoning becomes troubling when other symptoms occur such as gastrointestinal problems (nausea, vomiting and diarrhea), peripheral and central nervous system disorders (dysesthesia, ataxia, tremors, convulsions, paralysis, sleeplessness, hallucinations, and delirium), and cardiac problems, such as tachycardia and hypotension, lethargy, and coma) [33,34].…”
Section: Thallium Toxicitymentioning
confidence: 99%
“…Cardiac symptoms [33,34] Coma Hypotension Lethargy Tachycardia Dermatological symptoms [34] Alopecia (after about 3 weeks) Anhidrosis Hypohidrosis Mees lines on the nails (after about 1 month)…”
Section: Referencesmentioning
confidence: 99%
“…Finally, this study evaluated a wide range of concentrations, including the Tl concentrations found in the blood or urine of intoxicated people, which reached values of 8.3–880 μg/L and 68–42,000 μg/L or greater, respectively [ 19 , 55 , 56 ]. Additionally, we believe that high concentrations must be tested because Tl accumulates in different tissues and may be found at even higher concentrations than those detected in biological fluids.…”
Section: Discussionmentioning
confidence: 99%
“…The physico-chemical properties of the thallium like colorless, partially water soluble and tasteless along with its affordability makes it a pick for malicious criminal purposes. The oral dose of 10-15 mg/kg body weight in humans may prove to be lethal (Zavaliy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The physico-chemical properties of the thallium like colorless, partially water soluble and tasteless along with its affordability makes it a pick for malicious criminal purposes. The oral dose of 10-15 mg/kg body weight in humans may prove to be lethal (Zavaliy et al, 2021).Fatal as well as survival thallium toxicity is also reported in the pet or companion animals. The wide spectrum clinical manifestations of thallium poisoning mainly include painful severe gastroenteritis, neurological, dermatological (alopecia…”
mentioning
confidence: 99%